PENGARUH KOMPETENSI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI POLRES KABUPATEN WONOSOBO - Frida Widyawati Triasningrum; Diva Riza Fahlefi (JURNAL STIE SEMARANG, 2018)
Human resources are one element of the organization and have an important role in organizational activities. Therefore, human resources have to be managed in such a way that they are efficient and effective in achieving the organization's mission and goals. An organization is a system, namely a series and relationships between parts of a component that work together as a whole This research aims to analyze the influence of work competence, work discipline and work environment on the performance of employees at the Wonosobo District Police Station. This research uses three independent variables, namely work discipline competence and work environment, with one dependent variable, namely employee performance, The data within this research were collected through questionnaires and implemented to 66 police officers in Wonosobo as research samples, data testing techniques use quantitative analysis, namely, multiple linear regression analysis, determination coefficient and t test and model F test. Based on the result of data analysis, the research result shows that: competency variables have a positive and significant influence on employee performance, work discipline also has a significant influence and the greatest influence on employee performance. Work environment variables have a positive and significant influence on employee performance.